Towards a theory of whodunits murder rewritten - Percec, Dana 1976- (Cambridge Scholars Publishing, 2021)
Bringing together academics from Romania, the USA, Spain and Turkey, this volume follows the evolution of detective fiction, from its early forms during the late eighteenth century until its contemporary multi-media expressions. Tackling the best-known authors in the genre, as well as marginal, forgotten or eccentric names, and discussing prose which fits perfectly in the pattern of the genre or texts which have been conventionally associated with other genres, as well as films, the book explores the impact of whodunits in both highbrow and popular culture
Keywords: Kriminalroman; Detective and mystery stories / History and criticism; Detective and mystery films; Films de détective; Detective and mystery stories; Criticism, interpretation, etc